Digital future classroom for the inclusion of the NEET/Refugee population: proposal based on an ICT skills approach - Sardinha, Lara (2020)
School dropouts as well as the inclusion of refugee population in the host countries are in up-to-date. Vocational Education Training (VET) programmes have been developed under recent educational approaches. A new classroom physical space – the Future Classroom Lab - has been developed based on ICT resources and on non- traditional teaching/learning approaches. But are these suitable for the VET aiming the Non in Education, Employment or Training (NEET)/Refugee population as well as promoting the Inclusion and the Labour Market Integration (ILMI) of this population? The present research intends to investigate how a Digital Future Classroom (DFC) based on ICT skills approach promotes the ILMI of the NEET/Refugee population.